The Effect of Store Atmosphere on Impulse Buying and Positive Emotion as Intervening Variables at H&M Samarinda Stores - Dahlia Natalia; Rahmawati Rahmawati; Aji Sofyan Effendi (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this study is to analyze and prove the influence of Store Atmosphere on impulse buying, to analyze and prove the influence of Store Atmosphere on positive emotions, analyze and prove the influence of positive emotions on impulse buying, and to analyze and prove the influence of positive emotions in mediating the influence of Store Atmosphere. against impulse buying. This research was conducted at the H&M Store Samarinda. The research design uses an explanatory research approach. This type of research is quantitative. The population in this study are consumers who have made a purchase at the H&M Store Samarinda. Samples were taken as many as 130 people with non-probability sampling method, namely by using snowball sampling technique. Data was collected through the distribution of questionnaires. The data analysis technique used is the SEM method, namely PLS (Partial Least Square) with the help of Smart PLS software. The results showed that Store Atmosphere had a positive and significant effect on impulse buying, Store Atmosphere had a positive and significant effect on positive emotions, and positive emotions had a positive and significant effect on impulsive buying. This study also obtained positive and significant results between positive emotions mediating the influence of Store Atmosphere on impulse buying.